From the Frontline: Strengthening Surveillance and Response Capacities of the Rural Workforce in the Asia-Pacific Region. How Can Grass-Roots Implementation Research Help? - Larkins, Sarah; Carlisle, Karen; Harrington, Humpress; MacLaren, David; Lovo, Etivina; Harrington, Relmah; Fernandes Alves, Lucsendar; Rafai, Eric; Delai, Mere; Whittaker, Maxine (Frontiers in Public Health, 2020)
Health systems in the Asia-Pacific region are poorly prepared for pandemic threats, particularly in rural/provincial areas. Yet future emerging infectious diseases are highly likely to emerge in these rural/provincial areas, due to high levels of contact between animals and humans (domestically and through agricultural activities), over-stretched and under-resourced health systems, notably within the health workforce, and a diverse array of socio-cultural determinants of health. In order to optimally implement health security measures at the frontline of health services where the people are served, it is vital to build capacity at the local district and facility level to adapt national and global guidelines to local contexts, including health systems, and community and socio-cultural realities. During 2017/18 James Cook University (JCU) facilitated an implementation research training program (funded by Australian Department of Foreign Affairs and Trade) for rural/provincial and regional health and biosecurity workers and managers from Fiji, Indonesia, Papua New Guinea (PNG), Solomon Islands and Timor-Leste. This training was designed so frontline health workers could learn research in their workplace, with no funding other than workplace resources, on topics relevant to health security in their local setting. The program, based upon the WHO-TDR Structured Operational Research and Training IniTiative (SORT-IT) consists of three blocks of teaching and a small, workplace-based research project. Over 50 projects by health workers including surveillance staff, laboratory managers, disease control officers, and border security staff included: analysis and mapping of surveillance data, infection control, IHR readiness, prevention/response and outbreak investigation. Policy briefs written by participants have informed local, provincial and national health managers, policy makers and development partners and provided on-the-ground recommendations for improved practice and training. These policy briefs reflected the socio-cultural, health system and disease-specific realities of each context. The information in the policy briefs can be used collectively to assess and strengthen health workforce capacity in rural/provincial areas. The capacity to use robust but simple research tools for formative and evaluative purposes provides sustainable capacity in the health system, particularly the rural health workforce. This capacity improves responses to infectious diseases threats and builds resilience into fragile health systems.